Modern Programming : object oriented programming and best practices: deconstruct object-oriented programming and use it with other programming paradigms to build applications. - Lee, Graham, 1981- (Packt Publishing, Limited, 2019)
This book explores the complexity of object-oriented programming and addresses the central concepts of this important programming paradigm. You can use it as your easy reference guide to learn different development approaches and tools, helping you to work efficiently and make the leap to becoming an expert programmer.